Metodología para una correcta utilización de las tecnologías de la información y comunicación (T.I.C) en el bloque 6 la historieta del área de lengua y literatura; en las niñas y los niños de séptimo grado, de la escuela de educación general básica Zoila Alvarado de Jaramillo, de la parroquia San Sebastían, provincia de Loja, periodo lectivo 2013 – 2014 - Armijos Castillo, Ángel Vicente (2015)
This research entitled METHOD FOR PROPER USE OF INFORMATION TECHNOLOGY AND COMMUNICATION (TIC) in Block 6 "WORLDS" AREA OF LANGUAGE AND LITERATURE; IN GIRLS AND CHILDREN OF SEVENTH GRADE, SCHOOL EDUCATION GENERAL BASIC "ZOILA ALVARADO DE JARAMILLO" PARISH SAN SEBASTIAN, Loja province, school period 2013 - 2014, it had as its overall objective was to determine the importance of the applicat ion of a methodology for the correct use of information technology and communication (TIC) in Block 6 "Cartoon" in the area of Language and Literature; in girls and seventh graders, School of Basic General Education "Zoila Alvarado Jaramillo" by the San Sebastián province of Loja, parish school period 2013 - 2014, the same as was achieved by bringing the stage research to gather information for girls and parallel teaching seventh grade "C" through the application of surveys and interviews the teacher. The methodology allowed the development of scientific research was character, other complementary methods were inductive, deductive, descriptive, explanatory, statistical, based on the technique of the interview and its instrument survey questionnaire, which establishes the main conclusions and recommendations. To obtain the results of field research and contrasted with the theory, it was determined that the teacher does not have a broad domain knowledge and on using TIC to implement with their students and in turn causes large gaps in technological learning of these . One of the key recommendations stand out is updating the teacher in the management of TIC in order to be prepared to use these technological resources in the best way and to develop a methodology for the correct use of T IC by their students.